FATIGUE IN MULTIPLE SCLEROSIS – MECHANISMS, DIAGNOSIS, AND TREATMENT OPTIONS - Kornelia Kaźmierkiewicz-Makanga,; Weronika Spychalska,; Emilia Piotrowicz,; Filip Witowicz,; Julia Glińska,; Aleksandra Krawczyk,; Wiktoria Waldon,; Paulina Sumlet,; Maria Gofron,; Michał Duliński, (International Journal of Innovative Technologies in Social Science, 2025)
Fatigue is one of the most prevalent and debilitating symptoms of multiple sclerosis (MS), affecting up to 95% of patients and significantly impairing quality of life. This review synthesizes current knowledge on the pathophysiology, diagnosis, and treatment of MS-related fatigue. Fatigue in MS is a multidimensional phenomenon that includes physical, cognitive, and central components, stemming from both primary neurological mechanisms and secondary comorbidities. The underlying pathophysiological contributors include demyelination, dopaminergic dysregulation, pro-inflammatory cytokine activity, hypothalamic–pituitary–adrenal (HPA) axis dysfunction, and mitochondrial impairment. Diagnosis primarily relies on subjective self-report scales such as the Fatigue Severity Scale (FSS), Modified Fatigue Impact Scale (MFIS), and Fatigue Scale for Motor and Cognitive Functions (FSMC), though overlapping symptoms like depression and sleep disorders complicate clinical assessment. Treatment remains challenging: while pharmacological options—such as amantadine, modafinil, and ponesimod—offer limited and inconsistent benefits, non-pharmacological strategies, particularly physical activity and cognitive-behavioural therapy (CBT), show stronger evidence for improving fatigue and patient well-being. The paper emphasizes the necessity of an individualized, multidimensional treatment approach to effectively manage fatigue and mitigate its impact on the physical, social, and occupational functioning of individuals with MS.